The Effect of Cognitive Behavioral Therapy (CBT) on Reducing the Anxiety Level of Breast Cancer Patients Undergoing Chemotherapy at Hasanuddin University Hospital - Muh.Zukri Malik; I Kade Wijaya; Nirmala Amir; Atikah Asri Putri (Lembaga Penelitian dan Pengabdian Masyarakat Stikes Panrita Husada Bulukumba, 2022)
Breast cancer is the number one cancer in women in the world both globally and nationally. In Indonesia, breast cancer is in the top position of all types of cancer experienced by women in Indonesia. Cancer treatment is generally done by surgery and chemotherapy. Several studies describing the mental effects of breast cancer patients showed that 33.3% experienced anxiety. Psycho-educational interventions have proven effective in overcoming mental problems faced by patients with chronic illnesses such as cancer. One type of psycho-education that can be done includes Cognitive Behavioral Therapy (CBT). This study aims to determine the effect of Cognitive Behavioral Therapy (CBT) on Reducing the Anxiety Level of Breast Cancer Patients Undergoing Chemotherapy at Makassar City Hospital. This study used a Quasi-Experimental Design Pre-Post Test Design with Control Group. The results showed that the majority of respondents' anxiety before being given treatment had no anxiety/low anxiety in the intervention group and in the control group even though there were 16% of respondents who felt high anxiety. After treatment, the anxiety of the respondents in the intervention group remained the same as before the treatment and the anxiety of the respondents in the control group changed by 1 respondent (8.3%) who had experienced high anxiety decreased to moderate anxiety. Cognitive Behavioral Therapy (CBT) therapy did not show any significant results in reducing the patient's anxiety level. It is recommended that the CBT implementation session be maximized again to get maximum results.